A Peningkatan Tingkat Pengetahuan Kesiapsiagaan Bencana Siswa Setelah Diberi Edukasi Menggunakan Media Audio Visual Animasi di SMA 12 Semarang - mona saparwati; Trimawati Trimawati; Dewi Rosnita; Puji Lestari (Lembaga Pengembangan Kinerja Dosen, 2023)
Landslide is a disaster that occurs every year in Indonesia. Landslide disasters can result in complex losses, both loss of facilities and casualties. Landslides have the greatest impact on the most vulnerable groups, especially the children age group. This is because children directly experience, feel, and witness the impact caused by the age factor that is still immature psychologically. Efforts that can be made to reduce the impact of the disaster, one of which is to control the risk of landslides by increasing preparedness. This study provides education to students using audio- visual animation media which contains material on preparedness in the face of landslides. To determine the level of disaster preparedness knowledge of SMA 12 Semarang students before and after being given education using animated audio- visual It can be concluded that there is an increase in knowledge of disaster preparedness for students of SMA 12 Semarang before and after being given education using anıması audio- visual media. It is hoped that disaster preparedness education using animated media at SMA 12 Semarang can be applied continuously to students as an effort to anticipate disaster preparedness.